Lebih Berani di Dunia Maya: Self Disclosure, Safe Space, dan Media Sosial: Being Bolder Online: Self-Disclosure, Safe Spaces, and Social Media - Syadzilia Amanati; Nurul Ilmi Idrus (Emik : Jurnal Ilmiah Ilmu-Ilmu Sosial, 2026)
Self disclosure is a process in which a person intentionally reveals personal information, feelings, thoughts, or intimate experiences to another person, which are not normally known to the public. Studies on self-disclosure on social media generally focus on users' motivations for expression, while studies on safe spaces focus more on their role as safe spaces for expression. However, research examining the relationship between self-disclosure and safe spaces in the formation of digital identities and new interaction patterns on social media is still limited. This study aims to examine why users engage in self-disclosure on social media, how they interpret safe spaces, and how the two relate to shape digital identities and new interaction patterns. This qualitative research was conducted in Makassar. Data was collected using in-depth interview with ten informants aged between 19 and 23, who actively use social media in their everyday life and who had shared personal experiences, feelings, or sensitive opinions on social media platforms such as X, Instagram, and WhatsApp. The study indicates that self-disclosure occurs because of the need to express oneself, as the effort to maintain social relationships in digital spaces, and to search for a comfortable place to express oneself. Safe spaces are defined as spaces that allow users to express opinions, experiences, and feelings without fear of judgment, which are formed through a supportive audience, upload access controls, and protection of anonymity. The study indicates that self-disclosure occurs because of the need to express oneself, as the effort to maintain social relationships in digital spaces, and to search for a comfortable place to express oneself. Safe spaces are defined as spaces that allow users to express opinions, experiences, and feelings without fear of judgment, which are formed through a supportive audience, upload access controls, and protection of anonymity. This research also shows that self-disclosure occurring in a digital space perceived as safe encourages the formation of new, more fluid and responsive interaction patterns, while also enabling users to form flexible, situational, and continually negotiated digital identities. Thus, self-disclosure and safe spaces play a crucial role in shaping social media experiences in the digital age.